Safety and Tolerability of High-dose Inhaled Treprostinil in Pulmonary Hypertension. Issue 4 (April 2016) - Parikh, Kishan S.; Rajagopal, Sudarshan; Fortin, Terry; Tapson, Victor F.; Poms, Abby D.
Abstract : Abstract: Pulmonary arterial hypertension (PAH) has emerging therapeutic options including prostacyclin analogs. Inhaled therapy offers advantages compared with alternative routes of administration. We aimed to determine the safety and tolerability of inhaled treprostinil (iTRE) titrated to target maintenance dose higher than the labeled dose for PAH. Our study included 80 consecutive patients (69% female, 70% White) followed at the Duke University Medical Center prescribed iTRE at dose >9 breaths (54 μg). Etiology of pulmonary hypertension was most frequently PAH (51%) or secondary to lung disease (35%). Median follow-up was 20.3 months (interquartile range 14.2–33.2). Most patients (91%) had titrated iTRE dose to 12 breaths (72 μg) four times daily. Common side effects reported with drug initiation were cough (41%), headache (28%), and throat irritation (8%); most of the side effects improved at follow-up. Overall, 25% patients discontinued iTRE: 9 transitioned to parenteral therapy, 4 had untolerable side effects, 3 died, and 4 had other reasons. Overall, iTRE taken at a higher dose than approved for use in PAH was safe and well-tolerated in our cohort of pulmonary hypertension patients.